Reducing post-operative opioids in children undergoing outpatient urologic surgery: A quality improvement initiative - Mittal, Sameer; Shukla, Aseem R.; Sahadev, Ravindra; Lee, Seo Y.; Siu, Sharmayne; Gale, Erica M.; Plachter, Natalie; Srinivasan, Arun K. (Journal of pediatric urology, 2020)
Opioid prescriptions have been implicated as one of the proximate causes of the national opioid epidemic. Children and adolescents and their families are at risk for increased opioid exposure through prescriptions after surgery. In pediatric urologic surgery, indications for postoperative opioids can vary widely and a focus on opioid stewardship is important to reduce potential harms. To measure the efficacy of a quality improvement initiative aimed to reduce post-operative opioids for pain management in a large pediatric surgical cohort. Patients undergoing ambulatory pediatric urologic surgery at a tertiary children's hospital between July 2016 to June 2019 were analyzed. Structured physician peer-to-peer comparisons, electronic health record redesign and a standardized pain management protocol were implemented. Rate of opioid prescriptions per month, utilization of non-opioid analgesia, unplanned encounters in the emergency department and/or office during implementation were aggregated. Opioid doses and prescribed opioid days before and after protocol implementation were analyzed. A subcohort, from October–December 2018 was administered a patient-reported outcome questionnaire focused on pain management and return to baseline activity. A total of 6684 consecutive outpatient urologic cases were included (median age = 3.3 years old (IQR 0.9–9.2) and 92.3% male). Comparing 6 months pre-intervention and the post-intervention latest 6 month intervals, opioid prescription rate decreased from 43.9% to 2.3% (p < 0.001). Additionally, non-opioid analgesia with ketorolac increased from 30.7% to 50.6% (p < 0.001). Concurrently, no differences in the rate of office visits within 5 days, overall ED visits, ED visits for pain or for bleeding within 30 days after implementation were identified. Between October to December 2018, 373 cases were performed and a Patient-Reported Outcome (PRO) questionnaire was completed for 128 of those patients (34%). Families reported a low patient pain score of 3.7 (SD 2.4) and a rapid postoperative recovery time of a median 2 (IQR 1–4) days to full resumption of pre-operative level of activity. High satisfaction with opioid reduction in post-operative pain management was reported (median score of 10 (IQR 8–10)). Opioid prescriptions and utilization may be minimized without increasing unplanned encounters or adversely affecting quality of life. The QI framework utilized in this process can be implemented to reduce opioid exposure in other surgical patient populations. [Display omitted]